The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2217/fon.15.252
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Secondary Solid Malignancies after Allogeneic Hematopoietic Stem Cell Transplantation and Preventive Strategies

Abstract: The risk of secondary solid malignancies is increased after allogeneic hematopoietic stem cell transplantation (HSCT). The risk starts at about 10 years after HSCT and continues even 20 years later. The most common secondary malignancies include squamous cell carcinoma of skin, genitourinary tract and oral cavity; lung and breast cancers. The use of total body irradiation or conditioning chemotherapy, chronic graft-versus-host disease and duration since HSCT can influence the risk of secondary solid malignanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 55 publications
1
35
0
Order By: Relevance
“…[ 10 13 ] The majority of solid malignancies following allogeneic HSCT are SCC affecting skin, genitourinary tract, and oral cavity. [ 14 ] Rizzo et al analyzed 28,874 allogeneic HSCT patients and reported that people with GVHD have 5 times the incidence of SCC compared with the general population. [ 10 ] In the past, some investigators suggested that patients with Fanconi anemia have a higher risk of head and neck SCC with poor survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 13 ] The majority of solid malignancies following allogeneic HSCT are SCC affecting skin, genitourinary tract, and oral cavity. [ 14 ] Rizzo et al analyzed 28,874 allogeneic HSCT patients and reported that people with GVHD have 5 times the incidence of SCC compared with the general population. [ 10 ] In the past, some investigators suggested that patients with Fanconi anemia have a higher risk of head and neck SCC with poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…Although the source of the patient's carcinoma in situ is unknown, it may be the result of multifactorial interactions, including genetic predisposition, individual behaviors, long-terms effects of chemotherapeutic drugs and radiation, and viral infections. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Apel et al identified 7.4% of de novo non‐skin malignancies in kidney transplant recipients that represented breast cancer . The same is true for hematopoietic stem cell transplant recipients, whose risk for secondary solid malignancies is higher, with breast cancer being one of the most common .…”
Section: Introductionmentioning
confidence: 95%
“…HSCT conditioning regimens, like chemotherapy and/or radiotherapy, can play an important role in malignant transformation . Also, the risk of developing oral cancer after the transplantation increases over time . The incidence of subsequent solid tumors after HSCT is approximately 1% and 19%, whereas the rates at 10 years are between 2.2% and 6.1% .…”
Section: Risk Factors and Prevention Of Oscc In Famentioning
confidence: 99%
“…43 Also, the risk of developing oral cancer after the transplantation increases over time. 44 The incidence of subsequent solid tumors after HSCT is approximately 1% and 19%, whereas the rates at 10 years are between 2.2% and 6.1%. 45 In addition, individuals with FA who previously received HSCT had a 4.4-fold higher risk of developing HNSCC at a younger age.…”
Section: Risk Factors and Prevention Of Oscc In Famentioning
confidence: 99%